Snakes and Ladders Game Increases Counting Interest in Young Children: Permainan Ular Tangga Tingkatkan Minat Berhitung pada Anak Usia Dini - Seftina, Putri Jelita Trio; Aulina, Choirun Nisak (Indonesian Journal of Education Methods Development, 2025)
General Background: Early childhood education plays a crucial role in cognitive and skill development, where engaging learning methods are essential. Specific Background: Mathematical skills, particularly counting, are fundamental for early learners; however, conventional methods often fail to maintain children's interest. Knowledge Gap: Limited research explores the effectiveness of interactive games in fostering numeracy enthusiasm among preschoolers. Aims: This study aims to investigate the impact of the Snakes and Ladders game on enhancing counting interest in children aged 5–6 years at TK PKK Sendangagung. Results: A classroom action research (CAR) method was employed with 11 students, showing a significant increase in interest—from 7.38% in the pre-cycle to 35.79% in Cycle I and 81.25% in Cycle II. Novelty: Unlike previous studies, this research modifies the traditional Snakes and Ladders game by integrating movement-based learning, aligning with children's natural inclination toward play. Implications: The findings suggest that incorporating interactive and engaging educational tools can effectively boost children's motivation and cognitive development, providing a viable strategy for early childhood educators to enhance numeracy skills through play-based learning. Highlights: Interactive Learning Boosts Interest – The Snakes and Ladders game significantly enhances children's enthusiasm for learning to count, increasing engagement through play. Proven Effectiveness – Interest in counting rose from 7.38% (pre-cycle) to 81.25% (Cycle II), demonstrating the game's impact on early numeracy skills. Practical Implications for Educators – Play-based learning strategies can be an effective alternative to traditional methods, making math more enjoyable and accessible for young learners. Keywords: Interest Learning, Count, Old Children